2015
DOI: 10.1597/14-169
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Postoperative Edema in Alveolar Graft Performed with Bone Morphogenetic Protein (rhBMP-2)

Abstract: The facial edema was influenced by the rhBMP-2 used in alveolar graft, and trismus was proportional to the intensity of facial edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Recently, Leal et al has published a study regarding facial edema following alveolar cleft surgery with BMP-2 (1.5 mg/ml) in 150 patients [55]. They found maximal facial edema after 3 to 4 days, the edema was inversely proportional to age (p=0.003), more pronounced in females than in males (p=0.017) and there was a correlation between edema and reduced mouth opening (p=0.0002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Leal et al has published a study regarding facial edema following alveolar cleft surgery with BMP-2 (1.5 mg/ml) in 150 patients [55]. They found maximal facial edema after 3 to 4 days, the edema was inversely proportional to age (p=0.003), more pronounced in females than in males (p=0.017) and there was a correlation between edema and reduced mouth opening (p=0.0002).…”
Section: Discussionmentioning
confidence: 99%
“…the cranium, the mandibular symphysis or the tibia [47]. Since there are donor site morbidities (pain and scarring) and risks (bleeding, infection, nerve injuries, tibial fracture and dural tear) associated with any autologous donor site, bone substitutes have been studied to avoid these risks and to reduce surgery time and hospital stay [49][50][51][52][53][54][55]. Compared to other anatomical regions craniofacial bone reconstruction after trauma or tumor surgery and in anomalies is often complicated due to the complex form of facial bones and difficulties to cover large craniofacial bone defects [41,42].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the promising outcomes in several fields, systematic literature reviews demonstrated that, despite the adequate bone formation achieved by utilization of recombinant human bone morphogenetic protein 2 (rhBMP-2; INFUSE Bone Graft; Medtronic Sofamor Danek, Memphis, TN, USA), further research is needed (Guo et al, 2011;Van Hout et al, 2011). The greater facial edema without need of analgesic and antiinflammatory therapy was cited as a possible side effect associated with rhBMP-2 (Herford et al, 2007;Alonso et al, 2010;Carvalho, 2011;Leal et al, 2015), which indicates this protein as a viable alternative material for that purpose.…”
mentioning
confidence: 99%
“…Sparing children from the procedure of iliac crest harvesting is in itself a compelling reason to favor rhBMP2 use (Balaji, 2009). On the other hand, recent research revealed that facial edema was influenced by the rhBMP-2 used in alveolar graft, and trismus was proportional to the intensity of facial edema (Leal et al, 2014). The ideal substitute has not been discovered yet, but the investigative search continues (Coots, 2012).…”
Section: Discussionmentioning
confidence: 99%